The Nazis' last victims : the Holocaust in Hungary - Braham, Randolph L., 1922-2018 1922-2018 (Wayne State Univ. Press, 1998)
"The Nazis' Last Victims articulates and historically scrutinizes both the uniqueness and the universality of the Holocaust in Hungary, a topic often minimized in general works on the Holocaust. The result of the 1994 conference at the United States Holocaust Memorial Museum on the fiftieth anniversary of the deportation of Hungarian Jewry, this anthology examines the effects on Hungary as the last country to be invaded by the Germans."--BOOK JACKET. "The Jewish community in Hungary remained relatively intact throughout most of the Holocaust period until just months before the end of World War II. The Nazis' Last Victims questions what Hungarians knew of their impending fate and examines the heightened sense of tension and haunting drama in Hungary, where the largest single killing process of the Holocaust period occurred in the shortest amount of time."--BOOK JACKET.